The role of microductectomy in the diagnosis and treatment in women with pathologic nipple discharge - Kocaoğlu, Aytaç Emre; Altıntaş, Mehmet Mustafa; Mülküt, Fırat (The European Research Journal, 2022)
Objectives: Approximately one tenth of the patients who apply to the breast polyclinics complain of nipple discharge. Apart from pregnancy and lactation, spontaneous, unilateral, bloody or serous discharge originating from a single duct describes the Pathological Nipple Discharge (PND). The aim of this study is to show that precancerous breast lesions, which can be easily overlooked by conventional diagnostic methods, are detected with the microductectomy performed with the correct indication and it is possible to complete the appropriate treatment. Methods: Fifty-five microductectomy procedures were performed in 55 female patients who applied to the relevant clinic with the complaint of nipple discharge between January 2013 and August 2018 and who met at least two of the three criteria of pathological nipple discharge (spontaneous, single ductus, bloody or serous) except pregnancy and lactation. Prospectively collected information was evaluated retrospectively. Results: The average age of the patients in the study ranged from 23 to 73 years (mean age 45.5 years, median age 47 years). Out of 55 procedures, 28 (50.9%) were performed in women of reproductive age, 27 (49.1%) were performed in women in menopause. The discharge was localized to the right breast in 28 patients, and to the left breast in 27 patients. Forty-one of the 55 patients included in the study met all of the criteria for pathological nipple discharge, while the other 14 patients had at least two of the three criteria. Final pathologies were classified as follows; intraductal papilloma / papillomatosis with atypia, intraductal papillary carcinoma (IPC) and ductal carcinoma in situ (DCIS); Potential Neoplastic and Malignant Lesion (PNML). Conclusions: In cases where direct intraductal imaging methods cannot be applied in patients admitted to the polyclinic with pathological nipple discharge, microductectomy emerges as an effective diagnosis and treatment method that can be applied with low morbidity.